Synthesis and Multinuclear NMR Study of Novel Complexes of Zn(II) and Hg(II) Containing Phosphorus Ylides - Javad Sabounchei, Seyyed; Ahmadi Gharacheh, Mohsen; Hosseinzadeh, Marjan (Asian Journal of Chemistry, 2010)
Reaction of phosphorus ylides of the type R-COCH = PPh3 (R = C6H5C6H4 (1a) and C10H7 (1b)), with M(NO3)2.nH2O (M = Hg(II), n = 1 and Zn(II)), n = 6) in equimolar ratios using methanol as solvent are reported. The analytical data, IR, 1H, 13C and 31P NMR indicate a 1:1 stoichiometry between the ylides and M(II) nitrate [M = Zn(II) or Hg(II)] in each of new polymeric complexes of the type {Hg[(R-COCH = PPh3)(μ-NO3)(NO3)]}n. (DMSO)n (R = C6H5C6H4 (2a), C10H7 (2b)) and {Zn[(R-COCH = PPh3)(μ-NO3)(NO3)]}n.(DMSO)n (R = C6H5C6H4 (3a), C10H7 (3b)). Also, reaction of ylides with ZnCl2 in equimolar ratios, gave novel binuclear complexes of the type [(R-COCH = PPh3).ZnCl2]2 (R = C6H5C6H4 (4a), C10H7 (4b)). Variation of temperature in a 31P NMR study for complex 2a indicates that the disappearance of satellites, due to coupling to 199Hg, occurs with increasing temperature.